2019
DOI: 10.5194/gmd-12-3923-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leaf-level optical properties employed in land surface models

Abstract: Abstract. Vegetation optical properties have a direct impact on canopy absorption and scattering and are thus needed for modeling surface fluxes. Although plant functional type (PFT) classification varies between different land surface models (LSMs), their optical properties must be specified. The aim of this study is to revisit the “time-invariant optical properties table” of the Simple Biosphere (SiB) model (later referred to as the “SiB table”) presented 30 years ago by Dorman and Sellers (1989), which has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…These PFTs can be further classified as tropical (Tro), temperate (Tem) and boreal (Bor) by broad geoclimatic zones. Many current LSMs (e.g., the Community Land Model (CLM), the Jena Scheme of Atmosphere Biosphere Coupling in Hamburg (JSBACH), and the Joint United Kingdom Land Environment Simulator (JULES)) either rely on the "time-invariant optical properties look-up table" of the Simple Biosphere (SiB) model presented 30 years ago by Dorman and Sellers (1989) or lack references for the properties they do employ (Majasalmi and Bright, 2019). By examining the prescribed single-scattering albedo [SSA, i.e., the sum of reflectance (α) and transmittance (τ)] values of CLM (Lawrence et al, 2019), CoLM (Dai et al, 2003;Dai et al, 2004;Ji and Dai, 2010), Noah-Multi parameterization LSM (Noah-MP; Niu et al, 2011), JULES (Clark et al, 2011), SiB/SiB2 (Dorman and Sellers, 1989) and the Community Atmosphere Biosphere Land Exchange model (CABLE; Haverd et al, 2018), as shown in Figure 1, SSA values are very close to each other and almost identical to those in the SiB/SiB2 model.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These PFTs can be further classified as tropical (Tro), temperate (Tem) and boreal (Bor) by broad geoclimatic zones. Many current LSMs (e.g., the Community Land Model (CLM), the Jena Scheme of Atmosphere Biosphere Coupling in Hamburg (JSBACH), and the Joint United Kingdom Land Environment Simulator (JULES)) either rely on the "time-invariant optical properties look-up table" of the Simple Biosphere (SiB) model presented 30 years ago by Dorman and Sellers (1989) or lack references for the properties they do employ (Majasalmi and Bright, 2019). By examining the prescribed single-scattering albedo [SSA, i.e., the sum of reflectance (α) and transmittance (τ)] values of CLM (Lawrence et al, 2019), CoLM (Dai et al, 2003;Dai et al, 2004;Ji and Dai, 2010), Noah-Multi parameterization LSM (Noah-MP; Niu et al, 2011), JULES (Clark et al, 2011), SiB/SiB2 (Dorman and Sellers, 1989) and the Community Atmosphere Biosphere Land Exchange model (CABLE; Haverd et al, 2018), as shown in Figure 1, SSA values are very close to each other and almost identical to those in the SiB/SiB2 model.…”
Section: Introductionmentioning
confidence: 99%
“…The reported LOP values from early literature (e.g., Goudriaan, 1977;Dickinson, 1983) are different from those in the listed models (Figure 1). More recently, Majasalmi and Bright (2019) used various spectral databases to synthesize and harmonize the key optical property information of the PFT classification shared by many leading LSMs and found notable differences between the CLM default and measured LOP values in the NIR band. The LOP values for different PFTs provided by Majasalmi and Bright (2019) are highlighted in Figure 1 and referred to as "measured".…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations